Particle-antiparticle asymmetry in the B meson system - Aihara, Hiroaki (Physicist) (IOP ebooks. 2020 collection., 2020)
This book is a concise yet thorough study of charge-parity (CP) asymmetry, particularly within the B meson system. Beginning with an introduction to the topic, the book covers discrete symmetry, antiparticles and CP symmetry before moving on to CP violations in both the quark sector and the B meson system. It also examines the accelerators and experiments involved in unveiling the asymmetry within the weak interactions, and finishes with an outlook on investigations beyond the Standard Model. The book offers a fascinating insight into the research of CP asymmetry and is an essential reference for experimental physicists and other researchers related to the field.